2010
DOI: 10.1248/bpb.33.729
|View full text |Cite
|
Sign up to set email alerts
|

.BETA.-Citryl-L-glutamate Is an Endogenous Iron Chelator That Occurs Naturally in the Developing Brain

Abstract: The compound beta-citryl-L-glutamate (beta-CG) was initially isolated from developing brains, while it has also been found in high concentrations in testes and eyes. However, its functional roles are unclear. To evaluate its coordination with metal ions, we performed pH titration experiments. The stability constant, logbeta(pqr) for M(p)(beta-CG)(q)H(r) was calculated from pH titration data, which showed that beta-CG forms relatively strong complexes with Fe(III), Cu(II), Fe(II) and Zn(II). beta-CG was also fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
(57 reference statements)
0
17
0
Order By: Relevance
“…There is evidence in germinal cells for a role in spermatogenesis (9). BCG recently has been proposed to be an iron chelator (10).…”
mentioning
confidence: 99%
“…There is evidence in germinal cells for a role in spermatogenesis (9). BCG recently has been proposed to be an iron chelator (10).…”
mentioning
confidence: 99%
“…In addition, our previous findings suggested that b-CG is an endogenous low molecular weight Fe chelator. 6) It has been reported that citrate interacts with the fourth iron atom (Fe a ) of the [4Fe-4S] 2ϩ cubane cluster of aconitase in vitro 7) and prevents cluster disassembly, while it is also required for enzyme reactivation in rat cardiac mitochondria treated with H 2 O 2 . Recently, the mitochondrial matrix protein frataxin was also shown to play a role in the storage of iron within mitochondria and promote Fe(II) availability.…”
Section: Discussionmentioning
confidence: 99%
“…Using the same protocol as noted above, 2ϫ10 6 cells were cultured in 24-well plates for 3 d, then solubilized in 1 ml of lysis buffer (50 mM Tris-HCl, pH 8.0, 20 mM EDTA, 100 mM NaCl, 1% SDS). The solution was transferred into tubes and incubated with proteinase K (6 mg/ml) at 50°C for 2 h, then cooled on ice and incubated with RNase A (10 mg/ml) at 37°C for 30 min.…”
mentioning
confidence: 99%
“…As shown in Fig. 4C Recently, we found that β-citrylglutamate (β-CG), isolated from newborn rat brains, was an endogenous low molecular weight Fe chelator, 36) while the [Fe(II)(β-CG)] complex plays a role as an Fe-carrier for mitochondrial aconitase, and then activates it. 16) Therefore, we used the[Fe(II)(β-CG)] complex as an Fe-complex containing moderately bound Fe in our experiments.…”
Section: Comparison Of Effects Of Nitroprusside With Those Of Other Imentioning
confidence: 98%
“…46) Therefore, since the [Fe(II)(β-CG)] complex have a higher affinity to aconitase in mitochondria and can insert its Fe into the [3Fe-4S] cluster of aconitase, 16,36) it is considered that NO reacts with the Fe moiety of the [Fe(II)(β-CG)] complex, then forms an [(NO) Fe(II)(β-CG)] complex and reaches to mitochondria, resulting in activation of aconitase. β-CG seems to function as a tag addressed to aconitase in mitochondria, though further investigation is required to fully explain this interesting possibility.…”
Section: No]mentioning
confidence: 99%